DIGITAL COMIC CHRONICLE OF CALONARANG BALADEVA BY TANTRAZ COMICS BALI - Ida Bagus Kt. Trinawindu (Yayasan Sinergi Widya Nusantara, 2023)
Purpose: This digital comic of Trantraz Comic Studio is attractively packaged, displaying visuals different from other comics in Indonesia and able to provide new nuances in the story's packaging. The visual appearance is more contemporary and modern. Digital comics are digitally based on their delivery to readers. They are paperless in digital form, borderless because they are not limited in size or format and timeless because of their durability across time, which may not be possible in paper media. This research aims to explain and describe the meaning and ideology contained in digital comics by Tantraz Comics Bali. Research methods: An interpretative qualitative method is used in this research, emphasizing the disclosure of process and meaning in order to be able to capture a variety of qualitative information with descriptive clarity for a comprehensive conclusion in an interpretative manner. Findings: Comics have forms and types of stories and elements in comics in detail. Types of comics are educational comics, promotional comics, puppet comics and martial arts comics. In comics, there are themes, narratives, illustrations and character designs made by the demands of the story that reflect the nature and personality of the character. Implications: The ability to perform a work of art greatly influences the ability to digest and understand beauty.